Contamination of the hair of owned dogs with the eggs of Toxocara spp - HOLLAND, CELIA (My University, 2010)
Toxocara canis is one of the most common gastrointestinal helminthes of dogs. Humans can become infected through ingestion of infective eggs, Infection often causes few symptoms but in rare cases blindness can occur. It is generally accepted that human infection is caused as a result of direct contact with contaminated soil. However, recently, the eggs of Toxocara spp. have been found in the hair of dogs, implicating them as a possible additional route of transmission. The aim of this study was to assess the extent to which the hair of owned dogs was contaminated with the eggs of Toxocara. Samples were taken from the head, neck, back and anus of 184 dogs. Eggs were recovered from the hair using a previously standardised detection method. Eggs were found on the hair of 8.8% of the sampled dogs. None of the eggs found were embryonated. There was no significant difference found between the numbers or prevalence of eggs taken from the head, neck, back and anus. Older dogs were significantly more likely to possess eggs on their hair than those under one year of age. The low prevalence and the lack of potentially infective embryonated eggs suggests that direct contact with well cared for owned dogs poses a low risk of infection with T. canis.
PUBLISHED
Keywords: Zoology; Toxocara canis; Immunology, Inflammation & Infection